Euro Area Policies : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper discusses the risks of low growth and inflation over the medium term for the euro area. It examines the consequences of longer term trends that predate the crisis and the progress made in addressing the crisis legacies of high unemployment and debt. The paper illustrates, in a downside scenario, how low potential growth and crisis legacies leave the euro area vulnerable to the risks of stagnation. The weak medium-term prospect and limited policy space leave the euro area vulnerable to shocks that could lead to a prolonged period of low growth and inflation. Model simulations suggest that a modest shock to investor confidence could push up risk premia and real interest rates, as policy space is constrained at the zero lower bound and fiscal policy space to provide stimulus is limited. Moreover, the lingering crisis legacies of high debt and unemployment could amplify the original shocks, creating a bad feedback loop and keeping the economy stuck in equilibrium of stagnation.